2013
DOI: 10.1037/a0034653
|View full text |Cite
|
Sign up to set email alerts
|

Transient inactivation of the thalamic nucleus reuniens and rhomboid nucleus produces deficits of a working-memory dependent tactile-visual conditional discrimination task.

Abstract: Working memory depends on communication between the hippocampus and the prefrontal cortex (PFC); however, the neural circuitry that mediates interactions between these brain areas has not been well characterized. Two candidate structures are the thalamic reuniens (RE) and rhomboid (Rh) nuclei, which are reciprocally connected with both the hippocampus and PFC. These known anatomical connections suggest that RE/Rh may be involved in mediating hippocampal-prefrontal communication, and therefore may be critical f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
73
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(77 citation statements)
references
References 36 publications
4
73
0
Order By: Relevance
“…Our lab previously reported that inactivation of the nucleus reuniens/rhomboid nucleus (Re/Rh) impaired performance on the CD WM task, without impacting performance on the working-memory-independent CD STANDARD task (Hallock et al, 2013b). These midline thalamic nuclei are bidirectionally connected to both the hippocampus and mPFC (Cavdar et al, 2008; Vertes, 2002; Vertes, Hoover, Szigeti-Buck, & Leranth, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Our lab previously reported that inactivation of the nucleus reuniens/rhomboid nucleus (Re/Rh) impaired performance on the CD WM task, without impacting performance on the working-memory-independent CD STANDARD task (Hallock et al, 2013b). These midline thalamic nuclei are bidirectionally connected to both the hippocampus and mPFC (Cavdar et al, 2008; Vertes, 2002; Vertes, Hoover, Szigeti-Buck, & Leranth, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Based on these patterns of connections, several recent behavioral studies have examined the role of RE (and the dorsally adjacent rhomboid nucleus, RH) in various spatial working memory tasks (Hembrook and Mair, 2011; Hembrook et al, 2012; Loureiro et al, 2012; Cholvin et al, 2013; Hallock et al, 2013; Layfield et al, 2015). The general conclusion from these studies is that RE/RH is most directly involved in those tasks that involve the cooperative actions of the mPFC and the hippocampus (for review, Cassel et al, 2013; Vertes et al 2015; Griffin, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…A growing number of behavioural studies has provided evidence that RE is indeed involved in cognitive functions, most likely by coordinating neuronal activities in hippocampus and mPFC (Dolleman-van der Weel et al, 2009;Davoodi et al 2011;Eleore et al 2011;Hembrook et al 2011;Loureiro et al 2012;Prasad et al 2012;Cholvin et al 2013;Hallock et al 2013;Xu and Sűdhof 2013;Saalmann 2014;Bobal and Savage 2015;Ito et al 2015;Layfield et al 2015;Prasad et al 2016). Because mPFC lacks a direct return projection to the hippocampus (Sesack et al 1989;Jay and Witter 1991), RE might relay mPFC-processed information back to the hippocampus as part of a closed CA1-mPFC-RE-CA1 circuit Xu and Sűdhof 2013).…”
Section: Functional Relevancementioning
confidence: 99%
“…Recent studies have indicated the importance of RE for cognitive processes, such as behavioural flexibility, strategy shifting, inhibitory response control, associative learning, memory consolidation, working memory, fear memory, memory generalization, goal-directed navigation, and executive behaviours (Dollemanvan der Weel et al 2009;Davoodi et al 2011;Eleore et al 2011;Hembrook et al 2011;Kincheski et al 2012;Loureiro et al 2012;Cholvin et al 2013;Hallock et al 2013;Prasad et al 2013;Varela et al 2013;Wheeler et al 2013;Xu and Sűdhof 2013;Duan et al 2015;Griffin 2015;Ito et al 2015;Layfield et al 2015;Anderson et al 2015;Prasad et al 2016). This variety of memory-related behaviours has also been associated with the interplay between the medial prefrontal cortex (mPFC) and the hippocampus (Jin and Maren 2015).…”
Section: Introductionmentioning
confidence: 99%